The psychophysiological and health corollaries of child problem behaviours in caregivers of children with autism and ADHD. (24th July 2013) - Lovell, B.; Moss, M.; Wetherell, M. A.
Abstract Background The positive relationship between problem behaviours of children with additional complex needs and psychological distress in their caregivers has been widely evidenced. Fewer studies, however, have assessed the relationship between care recipients' problem behaviours and key physiological processes, relevant for the physical health status of their care providers. This study examined the psychological, endocrine and health corollaries of child problem behaviours in caregivers of children with autism and attention deficit hyperactivity disorder. Methods Caregivers (n = 18) completed self‐report measures of psychological distress, child problem behaviours and incidences of commonly occurring ailments. To capture important parameters of the basal diurnal cortisol pattern, caregivers collected saliva samples at waking, 30 min post waking, 1200 h and 2200 h on two consecutive weekdays. Results Data revealed a positive relationship between caregivers' perceived levels of stress and problems with child conduct behaviours. In addition, caregivers who reported more problems with child emotional and hyperactivity behaviours displayed atypical cortisol patterns characterised by flatter diurnal cortisol slopes and reduced cortisol awakening response magnitude. Subjective reports of commonly occurring ailments were also greater in caregivers experiencing more problems with child emotional behaviours. Conclusions These findings have implications for interventions that aim to improve the psychophysiological well‐being of the caregiver by targeting problem behaviours of the care recipient.